Numerical evaluation of Hankel transforms using Haar wavelets - Pandey R.K.; Singh O.P.; Singh V.K.; Singh D. (My University, 2025)
The aim of the article is to find an efficient algorithm for local numerical evaluation of Fn(p) by expressing the corresponding finite Hankel transform F̂n (p) in Haar series and truncating it. © 2010 Taylor & Francis.